1999
DOI: 10.1016/s0735-1097(99)00375-7
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-induced myocardial ischemia in isolated coronary artery ectasias and aneurysms (“dilated coronaropathy”)

Abstract: "Dilated coronaropathy" is an entity of nonobstructive, ischemic coronary artery disease. Nitroglycerin is of no therapeutic benefit but leads to an aggravation of exercise-induced CI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
222
0
20

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(248 citation statements)
references
References 38 publications
6
222
0
20
Order By: Relevance
“…This finding agrees with the results published in several previous studies, in which it has been widely shown that CAE co-exists with CAD approximately in 85% of cases [3,[13][14][15][16][17]. The right coronary artery was the most involved artery in the coronary artery ectasia followed by the anterior descending artery and the circumflex artery [2,13,18,19].…”
Section: Discussion:-supporting
confidence: 91%
“…This finding agrees with the results published in several previous studies, in which it has been widely shown that CAE co-exists with CAD approximately in 85% of cases [3,[13][14][15][16][17]. The right coronary artery was the most involved artery in the coronary artery ectasia followed by the anterior descending artery and the circumflex artery [2,13,18,19].…”
Section: Discussion:-supporting
confidence: 91%
“…In the literature, the phenomenon of SCF is well known for coronary artery ectasia (Kruger et al 1999;Senen et al 2004). Coronary artery ectasia is defined by segmental or diffuse dilation of the coronary arteries to more than 1.5 the diameter of the adjacent segments of the same artery or of different arteries (Swaye et al 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Nitrates theoretically seem to be appropriate in patients with CAE due to their ability to cause coronary dilatation, however on the contrary they have been shown to exacerbate myocardial ischemia. 5 Stent implantation is recommended only when significant stenosis accompanies the CAE and medical therapy has not been successful. This is because these lesions have heterogeneous morphologies, large caliber making it difficult to determine stent type, size and complete expansion.…”
Section: Discussionmentioning
confidence: 99%